THE SIGNIFICANT ROLE OF PSYCHOLOGY IN ISLAMIC EDUCATIONAL CONTEXTS - S Suharti; Eny Rahmawati; Kusti Puji Lestari (Proceeding of International Conference of Islamic Education, 2025)
This study examines the critical role of psychology in enriching the principles and practices of Islamic education. Rather than viewing psychology and religion as separate fields, this research highlights how psychological insights can complment Islamic values in promoting holistic human development. The qualitative descriptive approach was used to explore how psychological theories—particularly those related to learning, motivation, and emotional growth—can be adapted to Islamic educational contexts. Data were gathered through literature analysis and interviews with practitioners in both psychology and Islamic education. The findings reveal that when psychology is applied within an Islamic framework, it becomes a powerful tool to understand learners’ behavior, mental health, and spiritual needs. Such integration allows educators to address students not only as cognitive beings but also as moral and spiritual individuals. Moreover, it provides practical strategies for overcoming learning obstacles and fostering character development aligned with Islamic ethics. The study concludes that psychology, when harmonized with Islamic teachings, strengthens the educational process and supports the formation of well-balanced individuals. This implies a need for continuous dialogue between psychological sciences and Islamic pedagogy to build education systems that are both scientifically grounded and spiritually meaningful.